Efficacy of two PBO long lasting insecticidal nets against natural populations of Anopheles gambiae s.l. in experimental huts, Kolokopé, Togo. - Guillaume K Ketoh; Koffi M Ahadji-Dabla; Joseph Chabi; Adjovi D Amoudji; Georges Y Apetogbo; Fantchè Awokou; Isabelle A Glitho (PLoS ONE, 2018)
LLINs containing an insecticide plus the synergist, piperonyl butoxide (PBO) have been designed for increased efficacy against pyrethroid-resistant malaria vectors. In this study, two LLINs with PBO, PermaNet® 3.0 and Olyset® Plus, and a pyrethroid-only LLIN, Yorkool®, were evaluated in experimental huts against a free-flying, wild population of Anopheles gambiae s.l. in Kolokopé, a cotton cultivated area of Togo. WHO susceptibility tube tests and subsequent molecular assays determine the An. gambiae s.l. populations to be resistant to pyrethroids and DDT with both target site kdr and metabolic resistance mechanisms involved in the resistance observed. Anopheles gambiae s.s. and An. coluzzi were present in sympatry though the kdr (L1014F) mutation was observed at a higher frequency in An. gambiae s.s. The experimental hut results showed that both PermaNet® 3.0 and Olyset® Plus nets induced similar levels of deterrence, exophily, and reduced blood feeding rate against wild An. gambiae s.l. in contrast to the pyrethroid only LLIN, Yorkool®. The proportion of wild An. gambiae s.l. killed by unwashed PermaNet® 3.0 was significantly higher than unwashed Olyset® Plus (corrected mortality 80.5% compared to 66.6%). Similar blood feeding inhibition rates were observed for unwashed PermaNet® 3.0 and Olyset® Plus; however, PermaNet® 3.0 washed 20 times demonstrated significantly higher blood feeding inhibition rate than Olyset® Plus washed 20 times (91.1% compared with 85.6% respectively). Yorkool® performed the worst for all the parameters evaluated. In an area of pyrethroid resistance of An. gambiae s.l involving kdr target site and metabolic resistance mechanisms, LLINs with PBO can provide additional protection in terms of reduction in blood feeding and increase in mosquito mortality compared to a pyrethroid-only net, and should be considered in malaria vector control strategies.